Hubungan Perencanaan Karir Dengan Konsep Diri Siswa Kelas XII di SMAN 1 Ciledug - Cirebon Tahun Ajaran 2020/2021 - Ilham Fajar Rahmadi (Dharmas Education Journal (DE_Journal), 2021)
The problem in this research is that the students are still confused in planning their future careers, after graduating. Not only career planning, they also still experience confusion about their self-concept, they feel they have a low self-concept, see themselves as weak, feel doubtful, cannot take advantage of their talents or potential and lack self-confidence so they always view their self-concept negatively. The purpose of this study is to determine the relationship between career planning and self-concept of class XII students at SMAN 1 Ciledug. This study used a correlational quantitative approach to analyze data by connecting or data that has been collected as without intending to make generalized or generalized conclusions. The sample was taken using a saturated sample of 167 students. The research results show that a coefficient of 36.7%, which means that self-concept contributes 36.7% to career planning. Self-concept has a strong relationship to career planning. Students are able to consider their career decisions for the future after graduating because they are able to plan their careers well